2013
DOI: 10.5152/jaem.2013.21548
|View full text |Cite
|
Sign up to set email alerts
|

Why Speciality in Emergency Medicine is not Preferred?

Abstract: Bu toplantı raporu Sağlık Bakanlığı Sağlık Hizmetleri Genel Müdürlüğü'nün talebi üzerine ATUDER tarafından kurulan bir komisyon tarafından hazırlanmıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…The lack of security for ED physicians and the high rates of violence directed at them are cited as some of the most important reasons for why new physicians do not choose to practise this branch of medicine. 19 Looking at the age and experience of the physicians in our sample, we found that most were under the age of 40 and had been working at an ED for less than 10 years. This result likely arises from the fact that the emergency medicine specialisation is only 22 years old in Turkey.…”
Section: Discussionmentioning
confidence: 94%
“…The lack of security for ED physicians and the high rates of violence directed at them are cited as some of the most important reasons for why new physicians do not choose to practise this branch of medicine. 19 Looking at the age and experience of the physicians in our sample, we found that most were under the age of 40 and had been working at an ED for less than 10 years. This result likely arises from the fact that the emergency medicine specialisation is only 22 years old in Turkey.…”
Section: Discussionmentioning
confidence: 94%
“…18,19 Rate of reporting of violence was reported very low in study conducted in Turkey. 20 The lack of security in emergency for HCWs and the high rates of violence are some of the most important reasons why new generation is now getting attracted to choose to practice this branch of medicine. 21 Educational interventions especially in ED that aim to promote effective communication skills and use of de-escalation techniques to prevent patient aggression are certainly a useful strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Burnout level are directly related to the severity of the stress exposure on the individual. Therefore, burnout syndrome is more prevalent in professionals known to work under higher than “normal” levels of stress, including hospitals, and especially EDs …”
Section: Discussionmentioning
confidence: 99%